3. AIRPORT EMERGENCY DIESEL PREVENTIVE MAINTENANCE MANAGEMENT USING BATTERY INTERNAL RESISTANCE MONITORING ANALYSIS - Ahmad Ilham Kamal; Muchammad Furqon Muchaddats; Feti Fatonah; Djoko Herwanto; Desiana Putri; Sudibyo; Dikasitama (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
Emergency diesel generator is a very important system in every industry includingthe airport industry because this system supports the electricity of important equipment whena blackout occurs. in the emergency diesel generator system, there is a battery as a starter forthe diesel engine. if the battery capacity decreases, the diesel generator will not be able tostart the engine, therefore in the emergency diesel generator system, regular batterymaintenance is needed to maintain system reliability. in this journal, preventive maintenanceon the battery will be explained, especially on the emergency diesel generator system battery.one indicator of decreased capacity in the battery is an increase in its internal resistance value.in preventive battery maintenance, analyzing the increase in internal resistance can be areference for replacing a new battery.